2018
DOI: 10.1080/01425692.2018.1443432
|View full text |Cite
|
Sign up to set email alerts
|

Grammar schools in England: a new analysis of social segregation and academic outcomes

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 43 publications
2
41
0
4
Order By: Relevance
“…In Germany, 69 per cent of the curriculum in primary and secondary education is tracked, whereas in the UK, only 15 per cent of the curriculum is tracked (see Online Appendix Table A1). The between‐country differences in tracking may be complemented by countries offering exceptions from the predominant form of schooling (e.g., the United Kingdom has 163 selective grammar schools that diverge from the majority non‐selective comprehensive school system (Gorard and Siddiqui, )). Moreover, countries with a more comprehensive school system may implement numerous subtler forms of student tracking (see, e.g., Blossfeld et al ).…”
Section: Education and School Tracking As Central Elements Of Socialmentioning
confidence: 99%
See 1 more Smart Citation
“…In Germany, 69 per cent of the curriculum in primary and secondary education is tracked, whereas in the UK, only 15 per cent of the curriculum is tracked (see Online Appendix Table A1). The between‐country differences in tracking may be complemented by countries offering exceptions from the predominant form of schooling (e.g., the United Kingdom has 163 selective grammar schools that diverge from the majority non‐selective comprehensive school system (Gorard and Siddiqui, )). Moreover, countries with a more comprehensive school system may implement numerous subtler forms of student tracking (see, e.g., Blossfeld et al ).…”
Section: Education and School Tracking As Central Elements Of Socialmentioning
confidence: 99%
“…Studies analysing differences between school types, however, came to the conclusion that grammar schools would not foster social mobility or benefit children from lower‐class backgrounds. On the contrary, the recommendation was to phase out existing selective schools, indicating the importance of evaluating the impact of educational systems and their characteristics (see, for example, Burgess, Dickson and Macmillan, ; Boliver and Swift, ; Gorard and Siddiqui, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is no surprise then, that there has been a great deal of research examining how selective school systems affect educational achievement (e.g. Gorard & Siddiqui, 2018;Smith-Woolley et al, 2018). While examination results are no doubt important, recent research has drawn attention to competencies beyond academic achievement for determining pupil outcomes in later life (Brunello & Schlotter, 2011;Gutman & Schoon, 2013).…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
“…One exception is Gorard and Siddiqui’s () study, which did not account for school‐level prior attainment, but still found no positive grammar school effect. They noticed that adding ‘whether a pupil went to a grammar school or not’ did not improve the fitness of the model for predicting capped GCSE results.…”
Section: Previous Research On Grammar School Effectiveness Applying Tmentioning
confidence: 92%
“…Therefore, the results have limited relevance to today's schools and are not discussed. Total GCSE/GNVQ points score, The probability of obtaining 5 or more A*-C GCSE/GNVQ Indicator of outcome Coefficients Effect of grammar schools 6 grades on total GCSE/GNVQ or 25% more likely to achieve 5 A*-C on GCSE/GNVQ Harris and Rose (2013 The probability of obtaining 5 or more A*-C GCSE Indicator of outcome Coefficients Effect of grammar schools 10% more likely to achieve 5 A*-C on GCSE/GNVQ Gorard and Siddiqui (2018) Area Effectiveness of grammar schools in England 361 non-selective schools using all of the cases in the 11+ file (including those with the same combination of baseline variables). Pupil records in the 11+ file are still matched to the NPD based on characteristics, KS2 attainment and school type.…”
Section: Effectiveness Of Grammar Schools In England 357mentioning
confidence: 99%